Newly discovered miniature Microhyla from Borneo among the world’s smallest frogs - Das, Indraneil; Haas, Alexander
The terms ‘diminutive,’ ‘minute,’ or ‘miniature’ have been applied to a number of amphibian species that are under 15 mm (see Estrada and Hedges 1996; Biju et al. 2007; Duellman and Hedges 2008). The smallest amphibian species are members of the genera Eleutherodactylus (fide Estrada and Hedges 1996), Brachycephalus (fide Frost et al. 2006), Noblella (fide Lehr and Catenazzi 2009), and Stumpffia (fide Vences and Glaw 1991), and among Old World frogs, the smallest member of the microhylid genus Stumpffia of Madagascar, S. pygmaea, has an adult SVL range of 10.9–12.0 mm (Vences and Glaw 1991).